2019
DOI: 10.1590/0034-7167-2017-0620
|View full text |Cite
|
Sign up to set email alerts
|

Preconception health behaviors among women with planned pregnancies

Abstract: Objective: To identify determinants of preconception preparation among women with planned pregnancies. Method: A cross-sectional study with a probabilistic sample of 264 women between 18 and 49 years of age who had or were undergoing planned pregnancies, and were users of two School Health Centers in the city of São Paulo. Analysis was conducted through univariate and multiple logistic regression of three variable blocks: 1) social and demographic characteristics; 2) sexual and reproductive characteristics; 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
8
0
6
Order By: Relevance
“…Education enables women to develop the confidence needed to make decisions about their own body and health and to more easily understand the importance of the antenatal care services; in addition to the fact that a higher schooling level is generally related to greater autonomy in the decision to seek antenatal care. Other studies have also shown that women with more years of schooling are the ones who most perform preconception preparation and who experience less unplanned pregnancies ( 27 - 28 ) , events that are markedly related to better levels of maternal health. Therefore, investment in women’s education will benefit women and their fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Education enables women to develop the confidence needed to make decisions about their own body and health and to more easily understand the importance of the antenatal care services; in addition to the fact that a higher schooling level is generally related to greater autonomy in the decision to seek antenatal care. Other studies have also shown that women with more years of schooling are the ones who most perform preconception preparation and who experience less unplanned pregnancies ( 27 - 28 ) , events that are markedly related to better levels of maternal health. Therefore, investment in women’s education will benefit women and their fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Nursing professionals play an important role because health promotion spaces in primary care such as contraceptive consultations, cervical cytology collection, postnatal consultations and activities with adolescents in schools, represent a valuable opportunity to provide adequate contraceptive and preconception care ( 26 ) . In addition, these interventions should be aimed mainly at women from the most disadvantaged social groups ( 27 ) , as highlighted by the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this component, it is also mentioned that studies reiterate challenges to be overcome for the effective implementation of such actions, such as the scarcity of educational activities for SRH care; approach centered on the figure of the woman; content often limited to sexually transmitted infections; difficulty of adherence and participation of users in educational activities; need for welcoming and preconception care; absence of counseling and/or moments of dialogue with users who seek such assistance, and prescriptive conduct of professionals (2,(14)(15)(16)(17) .…”
Section: Actionmentioning
confidence: 99%
“…Articulation with other services and definition of strategies for carrying out health information and surveillance activities. Although scarce, studies already done show that inadequate physical spaces, lack of supplies, lack of trained human resources, work overload, fragmentation of care, moral and religious precepts, lack of communication in the care network and precariousness of physical facilities and working conditions are issues that directly influence the supply and quality of promotion activities and clinical care of SRH care in the context of primary care (4,11,(15)(16)(17) . These and other aspects, therefore, need to be considered in the context of public health and deepened in the scope of the construction of theoretical models, analysis, and evaluation of public policies.…”
Section: Theoretical Model -Clinical Care Component For Sexual and Re...mentioning
confidence: 99%